KEMAMPUAN GURU DAN MOTIVASI SISWA SERTA SARANA DAN PRASARANA DALAM PEMBELAJARAN PENJASORKES KELAS IV DAN V DI SD NEGERI 22 ANDALAS PADANG - Nia Purnama Sari (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this study was to determine the ability of teachers in teaching practices, student motivation and infrastructure in SD Negeri 22 Andalas Padang. This research use descriptive research, which uncovers and explains the implementation of the UKS in SD Negeri 22 Andalas Padang. Sampling technique used is total sampling which amounted to 57 people. Data collection tool was a questionnaire by using Guttman scale models. The results of the research is include the ability of teachers in the implementation of learning Penjasorkes obtained level of achievement by 70% in the classification enough. Motivation of studentsobtained the level of achievement by 73% in the classification enough, while at the infrastructure level of achievement gained by 60% in the less well classification.